Central American Higher Education Council (CSUCA) University Research Rankings: Elements towards an Improvement Strategy - Buitrago Reyes, Lesbia Jeannette (2021)
The objective of this study is to propose strategies for improvement of research positioning for universities pertaining to the Central American Higher Education Council (CSUCA). For this purpose, indicators of SCImago Institutions Ranking (SIR) and University Web Rankings (Webometrics) were analyzed as well as the positions held by CSUCA universities in 2020 in the aforementioned rankings. A quantitative approach was used to analyze the SIR IBER reports and in the Web Rankings in addition to examination of the academic-administrative structure of research activities based on the website for each university and visibility indicator monitoring. The first three positions for the SIR IBER correspond to the University of Costa Rica (UCR), the National University of Costa Rica (UNA) and the Technological Institute of Costa Rica (TEC), which, due to the number of articles published, also appear in the SIR World 2020 ranking. For University Web Rankings both on a global and Latin American regional scale, the University of Costa Rica (UCR) held first place, followed by the National University of Costa Rica (UNA), University of San Carlos de Guatemala (USAC), Technological Institute of Costa Rica (TEC), University of Panama (UP), Technological University of Panama (UTP), National Autonomous University of Honduras (UNAH), Autonomous University of Nicaragua, Managua (UNAN-Managua), University of El Salvador (UES) and Costa Rica´s State Distance University (UNED). For this type of analysis, greater focus on indicators with the highest weighting as well as updated web pages and metrics monitoring is required to better gauge research impact.